Welcome to the always-on world. - Agre, P.E (IEEE spectrum)
With the growth of new information and communications technologies, each human relationship is becoming a continual presence. You can exchange a dozen brief cell phone conversations with your spouse every day. You can keep track of your money through on-line banking. Your computer-mediated work activities can always be visible to your co-workers. This is a tremendous shift in human relationships: from episodic to always-on. The always-on world presents a series of challenges: interruptions-the ringing cell phone in the theater is just the start; divided attention-when every relationship is present everywhere, all the time, it becomes necessary to juggle commitments; addiction-some people can't stop reading their e-mail; boundaries-parents often give their children beepers or cell phones to keep track of them, which is disturbing to many children; other new technologies-for example, electronic payments-make other kinds of tracking possible as well. The always-on world is a world of freedom, but it is also a world of anonymous global forces that ceaselessly rearrange all relationships to their liking. We don't understand this world very well, but there will soon be plenty of opportunity to study it first-hand